2018
DOI: 10.1097/corr.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Tranexamic Acid Reduces Postoperative Blood Loss After High Tibial Osteotomy

Abstract: Level III, therapeutic study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(87 citation statements)
references
References 20 publications
2
85
0
Order By: Relevance
“…It has achieved good results in TKA and total hip arthroplasty (THA). However, few studies have been conducted on the role of TXA in HTO, and most of the research has only concentrated on the effects of intravenous or topical application alone on blood loss. The aim of the present study was to explore the efficacy and safety of the combined administration of TXA after HTO.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has achieved good results in TKA and total hip arthroplasty (THA). However, few studies have been conducted on the role of TXA in HTO, and most of the research has only concentrated on the effects of intravenous or topical application alone on blood loss. The aim of the present study was to explore the efficacy and safety of the combined administration of TXA after HTO.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that the decrease in the drainage volume and hemoglobin 1 day after the operation in the TXA group was lower than that in the solo group, and the difference was statistically significant ( P < 0.05). Through a retrospective study of 66 HTO patients, Palanisamy et al found that intravenous administration 10 minutes before application of the tourniquet and intravenous administration of TXA 3 h after the operation could reduce blood loss. In another retrospective study, Kim et al injected TXA at a dose of 10 mg/kg before and 6 h after tourniquet application and 24 h after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations